BASIC LIFE TASKS (Annual of the Faculty of Philosophy in Skopje, 2011)
People everyday assign tasks and are engaged in their realization. Human life is primarily realization of tasks. Tasks are numerous and various (official, private, social, small, big, easy, hard, etc.). Parts of the tasks are general for all people, but their characteristics and the way of their realization vary ; the realization of tasks is individualized. The basic purpose of the personality is realization of life tasks. Tasks are personally and socially determined. Their realization has various and numerous effects, including transformation of person and reality. Four long-term tasks are: well-being/happiness, working and doing, relating with others (especially love and partnership), and personal development, self- realization and self-perfection.